Metabolism and disposition of [14C]dimethylamine borane in male Harlan Sprague Dawley rats following gavage administration, intravenous administration and dermal application. (January 2014) - Mathews, James M.; Watson, Scott L.; Patel, Purvi R.; Black, Sherry R.; Hong, Yan; Levine, Keith E.; Ross, Glenn; Germolec, Dori R.; Thakur, Sheetal A.; Waidyanatha, Suramya
Abstract 1. <?ri?>Dimethylamine borane (DMAB) is used as a reducing agent in the manufacturing of a variety of products and in chemical synthesis. National Toxicology Program is evaluating the toxicity of DMAB in rodents following dermal application. The objective of this study was to evaluate the metabolism and disposition of DMAB in male Harlan Sprague Dawley (HSD) rats. 2. <?ri?>Disposition of radioactivity was similar between gavage and intravenous administration of 1.5 mg/kg [14C] DMAB, with nearly 84%–89% of the administered radioactivity recovered in urine 24 h post dosing. At 72 h, only 1% or less was recovered in feces, 0.3% as CO2, and 0.5%–1.4% as volatiles and 0.3%–0.4 % in tissues. 3. <?ri?>The absorption of [14C]DMAB following dermal application was moderate; percent dose absorbed increased with the dose, with 23%, 32% and 46% of dose absorbed at 0.15, 1.5 and 15 mg/kg, respectively. Urinary and fecal excretion ranged from 18%–37% and 2%–4% of dose, respectively, and 0.1%–0.2% as CO2, and 1%–3% as volatiles. Tissue retention of the radiolabel was low ∼1%, but was higher than following the gavage or intravenous administration. 4. <?ri?>Following co-adminsitration of DMAB and sodium nitrite by gavage, N-nitrosodimethylamine was not detected in blood or urine above the limit of quantitation of the analytical method of 10 ng/mL. 5. <?ri?>Absorption of DMAB in fresh human skin in vitro was ∼41% of the applied dose: the analysis of the receptor fluid shows that the intact DMAB complex can be absorbed through the skin.